Budaya Mamanda, Konsep, Filosofi, Identitas Dan Nilai-Nilai Pendidikan Islam - Ghina Sofia Mahfuzah; Zulfa Jamalie; Fasih Wibowo (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
Mamanda is a form of traditional folk theater from the Banjar community that serves not only as entertainment but also as a means of conveying moral, social, and religious values. This article aims to explore the concept, philosophy, cultural identity, and Islamic educational values embedded in Mamanda art. The research uses a qualitative-descriptive approach through literature studies of books, journal articles, and written sources related to the Mamanda culture. The findings indicate that Mamanda emerged from the social construction of the Banjar community, which had a strong curiosity about royal life, thus being presented with a royal palace setting and symbolic royal characters. Mamanda features a performing arts concept developed from the influence of Malay and local Banjar cultures, with a distinctive performance structure. The philosophy of Mamanda reflects the worldview of the religious, democratic, educational, and aesthetic Banjar people, while upholding the importance of togetherness. The cultural identity of Mamanda is evident through the use of Banjar and Malay Banjar languages, traditional costumes, music, and accompanying dances. Additionally, Mamanda contains Islamic educational values and character education such as religiosity, honesty, responsibility, discipline, social concern, and the spirit of togetherness. Thus, Mamanda holds great potential as an Islamic education medium based on local culture, while also serving as a means to preserve the local wisdom of the Banjar community.